Dignity of dying patients in Buddhist and Catholic ethics: Divergence and Convergence - Daodee, Supaporn (Studia Bioethica, 2013)
This article is mainly based upon documentary study that has examined religious texts regarding the doctrines and the ethics of dignity of human life in Theravada Buddhism and Catholicism. It attempts to see what is common in the teachings of these two religions concerning the dignity of life at the terminal stage. The purpose is twofold: first, to develop an understanding of the dignity of life and the convergence and divergence in Theravada Buddhist ethics and Catholic ethics and second, to contribute the practical application in making proper decisions on dignity of the dying within these two religions.